Variations of Movement, Dispersal, and Morphometrics among Subpopulations of Javan Endemic Damselfly, Drepanosticta spatulifera (Odonata: Platystictidae) in Petungkriyono Forest - Amelia Nugrahaningrum; R.C. Hidayat Soesilohadi (Universitas Gadjah Mada, 2021)
Drepanosticta spatulifera is a Javan endemic damselfly. The population is spread unevenly in the Petungkriyono Forest and is threatened due to environmental pressure. The aims of this research are to know the variation of the movement, dispersal, and morphometric among subpopulations of D. spatulifera. Movement and dispersal variation data collection was done using Mark Release Recapture (MRR) for six weeks from early August until mid-September 2020. The collection of morphometric samples was done during the last week of the MRR survey and 46 individuals were measured with 12 continuous characters. During the MRR survey, 596 males of D. spatulifera were marked and 302 were recaptured. D. spatulifera had short movement and dispersal thus no individuals were found across the subpopulations. The distance moved of successive capture and net lifetime movement were dominantly less or equal to five meters. The duration of the MRR survey had a low correlation with the dispersal distance of D. spatulifera. In the morphometric variations, closer subpopulations tended to have a similar cluster of morphometric characters. Variation of distance moved between successive capture and wing size from Mangli Stream was significantly different from other sites. The subpopulation of Mangli, the farthest and higher altitude of the sites, had the highest distance move, more disperse, and the largest wing size. Our study showed that D. spatulifera was extremely sedentary damselfly. It will enhance inbreeding and vulnerability to extinction. Therefore, the interaction between the subpopulations of D. spatulifera in the Petungkriyono Forest needs to be done more.